Modelling and experimental validation of enantioseparation of racemic phenylalanine via a hollow fibre-supported liquid membrane - Prapasawat, Tatchanok; Lothongkum, Anchaleeporn Waritswat; Pancharoen, Ura (My University, 2014)
This paper reports on the enantioseparation of racemic phenylalanine or D-phenylalanine and Lphenylalanine via a hollow fibre-supported liquid membrane (HFSLM) and the results are compared with the mathematical model. The enantioseparation results, of 80 % and 73 %, showed the highest extraction and stripping of l-phenylalanine from the feed phase and the enantiomeric excess (% ee) of 60 % from 6 mmol L-1 of initial rac-phenylalanine in the feed solution. The optimum parameters were feed solution at pH 5, 6 mmol L L-1 of O,O′-dibenzoyl-(2S,3S)-tartaric acid ((+)-DBTA) as the extractant in octanol as the liquid membrane, and deionised water as the stripping solution. Equal flow-rates of feed and stripping solutions of 100 mL minL-1 were adjusted in a batch operation mode for 50 min at ambient temperature. From the calculation, the equilibrium constants of extraction (K ex) and mass transfer coefficients in the feed phase (k f) and in the liquid membrane phase (k m) were found to be 1.81 L mmol-2, 3.50 × 10-2 cm s-1, and 1.40 × 10-2 cm s-1, respectively. Finally, the change in concentrations of d,l-phenylalanine over time in the feed and stripping solutions by mathematical model were estimated and compared with the experimental results. The values thus calculated were in agreement with the experimental data with the average deviation of approximately 3 %. © 2013 Institute of Chemistry, Slovak Academy of Sciences.
Keywords: d,l-phenylalanine; enantioseparation; hollow fibre-supported liquid membrane; model; O,O′-dibenzoyl-(2S,3S)-tartaric acid; rac-phenylalanine